Rekrutmen Dosen dan Tenaga Kependidikan di STKIP PGRI Lubuklinggau - M. Rusni Eka Putra; Marianita Marianita; Ahmad Gawdy Prananosa (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
The purpose of this study was to determine the recruitment of lecturers and education personnel at STKIP PGRI Lubuklinggau. This study uses a qualitative approach with qualitative descriptive methods. The results of the study, Recruitment of lecturers and education staff at STKIP PGRI Lubklinggau include; setting standards, implementing recruitment, evaluating, controlling and improving quality. Determination of lecturer recruitment standards involves all related units such as quality assurance institutions, majors, study programs, the head of staffing and the general administrative body, the chairman and vice chairman. The recruitment depends on the needs of lecturers and education personnel in each study program, which is to meet the needs of the ratio of lecturers and students. Conclusions, the recruitment of lecturers and education staff at STKIP PGRI Lubklinggau includes; setting standards, implementing recruitment, evaluating, controlling and improving quality. Keywords: Recruitment, Lecturers and Education Personnel